DESIGN OF VOICE CONTROL SYSTEM AN ANDROID AND ARDUINO-ASSISTED AS A COMPONENT ACTIVATION ON VEHICLES - Wachid Yahya; Canggih Ajika Pamungkas (VANOS Journal of Mechanical Engineering Education, 2019)
The purpose of this research was to design an Android and Arduino-assisted voice control system as a component activation on vehicles.  The method in this study are; making initial design concepts, procuring tools and materials, manufacturing products, testing products, and analyzing product performance. The conclusion of this research is that this system has gone through the application design stage on android using MIT App Inventor 2 and making the program using Arduino IDE, and the last stage is product testing. The test results show that the application installed on an android smartphone is able to work properly. The design of the program on a microcontroller using Arduino was also successfully compiled. This voice control vehicle module achieves connectivity capability with bluetooth as far as 14 meters. Accuracy of voice commands in the range of 73-95%, this result was obtained using clear voice articulation according to acceptance in google speech and using good internet network connectivity. Able to activate and turn off vehicle door locks, hazard, alarm, and engine.